The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1002/tea.20031
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry in interaction: How local adaptations of curricula shape classroom communities

Abstract: In this study, we seek a better understanding of how individuals and their daily interactions shape and reshape social structures that constitute a classroom community. Moreover, we provide insight into how discourse and classroom interactions shape the nature of a learning community, as well as which aspects of the classroom culture may be consequential for learning. The participants in this study include two teachers who are implementing a new environmental science program, Global Learning through Observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 52 publications
1
73
0
3
Order By: Relevance
“…These differences may have contributed to differential learning outcomes for the students (Enyedy & Goldberg, 2004). As a result, our research focus branched and we began to pursue the following research questions: What accounts for the observed differences in these two teachers' practice?…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These differences may have contributed to differential learning outcomes for the students (Enyedy & Goldberg, 2004). As a result, our research focus branched and we began to pursue the following research questions: What accounts for the observed differences in these two teachers' practice?…”
Section: Methodsmentioning
confidence: 99%
“…In a previous paper, Enyedy and Goldberg (2004) document the divergent classroom practices of these two teachers and the subsequent learning outcomes for the students. We argue, however, that a focus on classroom practice and outcomes is an important, but limited aspect of what we, as a field, need to consider when attempting understanding of the complexities of teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a substantial amount of research has focused on in-service teachers' use of science and mathematics curriculum materials (Collopy, 2003;Enyedy & Goldberg, 2004;Fishman, Marx, Best, & Tal, 2003;Lloyd, 1999;Pintó, 2004;Remillard, 1999;Remillard & Bryans, 2004;Roehrig & Kruse, 2005;Schneider et al, 2005), only recently has research begun to explore preservice elementary teachers' use of and learning from science curriculum materials (Davis, 2006;Dietz & Davis, in press;Schwarz et al, in press). The results presented here extend this research by examining preservice elementary teachers' relationships with science curriculum materials through the lens of identity.…”
Section: Introductionmentioning
confidence: 99%